Parental Inputs and Socio-Economic Gaps in Early Child Development - Lindsey Macmillan; Emma Tominey (Institute of Labor Economics (IZA), 2019)
By the time children start school, socio-economic gaps are evident in child skills. We document a causal effect of a reform to mothers' education on her child's skills and use mediation analysis to explore the role of parental inputs as mechanisms. The reform shifted mothers' education from no, to a low level of qualifications. Our results suggest that financial resources are an important channel, explaining up to 59% of the effect on child cognitive skills. On top of this, parental investments of health behaviours during pregnancy and monetary investments at home explain a further 14% of the test score gaps.
Keywords: I24; J13; D10; 330; child development; test scores; socio-emotional skills; parental inputs; decomposition; ALSPAC